NC palladacycles in the Heck arylation of ethylene: synthesis, structure and their reactivity - Atla, Shashi B.; Kelkar, Ashutosh A.; Puranik, Vedavati G.; Bensch, Wolfgang; Chaudhari, Raghunath V. (Journal of Organometallic Chemistry, 2009)
Monomeric cyclopalladated complexes with NC coordination using ligands 2-phenylpyridine, 2-phenylquinoline, 8-methylquinoline have been synthesized and the structures have been determined by single crystal X-ray structure analysis. The crystal structures of monomeric palladacycles prepared using benzophenone oxime, and 2-phenylpyridine have also been determined. The use of these complexes in the Heck arylation of ethylene with 2-bromo-6-methoxynaphthalne (BMN) to give 2-vinyl-6-methoxynapthalene which is an intermediate for the synthesis of anti-inflammatory drug Naproxen has been examined and also arylation of ethylene with 3-bromo-benzophenone and 4-bromo-isobutylbenzene was investigated. These palladacycles with NC coordination show excellent catalytic activity with a TOF > 4000 h (1). (C) 2008 Elsevier B.V. All rights reserved.
Keywords: alpha-Aryl propionic acids; Arylation; Palladacycle

Novel foldamer structural architecture from cofacial aromatic building blocks - Prabhakaran, Panchami; Puranik, Vedavati G.; Chandran, Jima N.; Rajamohanan, Pattuparampil R.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Chemical Communications, 2009)
This communication demonstrates the utility of peri-substituted 1,8-diphenylnaphthalene as an effective building block for the construction of novel conformationally ordered synthetic oligomers displaying cofacial structural features.

New synthetic route for 1,2-diketo compounds using unexpected C-C bond cleavage by PCC - Bhosale, Shrikar M.; Momin, Aadil A.; Gawade, Rupesh L.; Puranik, Vedavati G.; Kusurkar, Radhika S. (Tetrahedron Letters, 2012)
An efficient method has been established for the preparation of 1,2-diketones by unexpected C-C bond cleavage in 4-keto-2-hydroxy esters using pyridiniumchlorochromate (PCC). (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: 1; 2-Diketones; C-C bond cleavage; PCC

New dipyranocoumarin from the leaves of calophyllum apetalum willd - Joshi, Swati P.; Kulkarni, Smita R.; Phalgune, Usha D.; Puranik, Vedavati G. (Natural Product Research, 2013)
A new dipyranocoumarin, -hydroxytomentolide A (1) was isolated from the leaves of Calophyllum apetalum together with the known compounds friedelin (2), apetalactone (3), inophyllum C (4) and canophyllol (5). The structure of the new compound was established by spectroscopic studies which include H-1 NMR, C-13 NMR, NOESY, HetCOSY, COLOC experiments and single crystal X-ray diffraction analysis.
Keywords: -hydroxytomentolide A; Calophyllum apetalum; dipyranocoumarins; Guttiferae; Triterpenoids

NHC-Catalyzed reaction of enals with hydroxy chalcones: diastereoselective synthesis of functionalized coumarins - Bhunia, Anup; Patra, Atanu; Puranik, Vedavati G.; Biju, Akkattu T. (Organic Letters, 2013)
The N-heterocyclic carbene-catalyzed annulation of enals with 2'-hydroxy chalcones afford cyclopentane-fused coumarin derivatives with an excellent level of diastereocontrol. The reaction tolerates a broad range of functional groups; 25 examples are given, and a preliminary mechanistic investigation is provided.

Nucleophilic ring-opening of benzoxazinones by dbu: some observations - Baravkar, Sachin B.; Roy, Arup; Gawade, Rupesh L.; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Synthetic Communications, 2014)
This communication demonstrates the formation of an unusual nucleophilic ring opening of benzoxazinones by 1,8-diazabicycloundec-7-ene (DBU). This observation contradicts the intrinsic feature of a hindered nonnucleophilic base like DBU. Confirmation of the product was achieved via single-crystal X-ray diffraction studies.
Keywords: Benzoxazinones; caprolactam; DBU; HATU

New pimarane diterpenes and other antimycobacterial metabolites from anisochilus verticillatus - Kulkarni, Roshan R.; Shurpali, Ketaki; Khedkar, Vijay M.; Puranik, Vedavati G.; Sarkar, Dhiman; Joshi, Swati P. (Natural Product Research, 2016)
Phytochemical investigation of the acetone extract of the aerial parts of Anisochilus verticillatus afforded a new 8,9-secopimarane diterpene (1), two new isopimarane diterpenes (2, 3) and the known ursolic acid (4), beta-amyrin (5), -amyrin (6), stigmast-5-en-3-one (7) and hydroxychavicol (8). Structures of the new compounds were elucidated with the help of 1D and 2D nuclear magnetic resonance spectroscopic data, and single crystal X-ray crystallography of compound 3. Compounds 2 and 8 inhibited Mycobacterium tuberculosis H37Ra with an IC50 of 11.3 (IC90 of 20.0g/mL) and 12.5g/mL, respectively. Correspondingly, molecular docking studies with Extra Precision Glide revealed a correlation between score and biological activity for these compounds to describe the molecular basis for the most significant SAR results.
Keywords: alanine racemase; Anisochilus verticillatus; antimycobacterial activity; diterpenes; Lamiaceae